SUBJECT OF FORENSIC TACTICS (Bulletin of criminological association of Ukraine, 2024)
In this article, it has been emphasized that it is impossible to talk about the development of tactical and forensic support for pre-trial investigation without clarifying the general provisions of forensic tactics. Especially, taking into account the fact that today the question of its legal nature is debatable, which, in turn, is due to the lack of unified and clear views on the subject of forensic tactics. An analysis of scientific approaches to the interpretation of forensic tactics has been carried out. It has been found that in the content of the concept of “forensic tactics”, in most cases, its subject is also laid down. It has been noted that as a subject of forensic tactics, a set of methods and recommendations of practical actions to combat crime is considered. It has been proposed to understand the subject of forensic tactics as a set of scientifically based techniques and recommendations, as well as practical actions of authorized subjects, aimed at ensuring the fulfillment of the tasks of criminal proceedings, prevention and countermeasures of criminal offenses defined in the prescriptions of the criminal procedural legislation. With this in mind, forensic tactics has been proposed to be understood as an independent part of the science of forensics, which establishes a set of scientifically based methods, recommendations and practical actions defined in the provisions of the criminal procedural legislation, aimed at collecting, accumulating, processing, researching and using evidentiary information, influencing the behavior of a person, in order to ensure the fulfillment of the tasks of criminal proceedings, prevention and counteraction of criminal offenses.
Keywords: forensic tactics; forensics; concept; subject; essence; techniques; recommendations